COMPILING OF MATERIAL INTO SEPARATE PACKAGES FOR TAXES AND PUBLIC SMOKING - SMS (Tufts Archival Research Center, 2007)
CONFIDENTIAL; Marginalia; Report prepared for an upcoming briefing. Includes material addressing issues around cigarette tax, social cost, and public smoking/indoor air quality (IAQ). Discusses workplace smoking and the different types of workplace smoking kits.